2015
DOI: 10.1515/supcat-2015-0001
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Activity of Gold and Silver Nanoparticles Supported on Zinc Oxide

Abstract: Gold (AuNPs) and silver (AgNPs) nanoparticles have been prepared by “one-pot” synthetic method in the presence of poly(N-vinylpyrrolidone) (PVP). Absorption spectra, size, morphology, and structure of AuNPs and AgNPs were studied by UV-Vis spectroscopy, DLS, SEM, and TEM. According to DLS measurements the average sizes of metal nanoparticles stabilized by PVP in aqueous solution are varied from 10 to 25 nm for AuNPs and from 6.5 to 44 nm for AgNPs. The impregnation method is used to support AuNPs and AgNPs on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Decomposition of H 2 O 2 was carried out in thermostated glass reactor equipped by magnetic stirrer . Thin powders of PV 7 /TiO 2 and PV 50 /TiO 2 were dispersed in 0.9 mL aqueous solution of H 2 O 2 and the volume of released oxygen was measured by burette at definite time interval.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Decomposition of H 2 O 2 was carried out in thermostated glass reactor equipped by magnetic stirrer . Thin powders of PV 7 /TiO 2 and PV 50 /TiO 2 were dispersed in 0.9 mL aqueous solution of H 2 O 2 and the volume of released oxygen was measured by burette at definite time interval.…”
Section: Resultsmentioning
confidence: 99%
“…Both decomposition of hydrogen peroxide and oxidation of oxylene in the presence of catalysts were carried out in a glass reactor described in. [15] The X-ray diffractometer (PANanalytical, X'Pert Pro) was used for identification of TiO 2 and catalyst phases and determination of their average crystal size. The XRD data were interpreted on the basis of Bragg's equation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that polymer‐protected AuNPs convert 4‐nitrophenol to 4‐aminophenol with high yield (97‐99% conversion). The catalytic activity of PVP‐AuNPs supported on the surface of aluminum oxide was evaluated with respect to decomposition of hydrogen peroxide …”
Section: Introductionmentioning
confidence: 99%